Remarks to the G20 Finance Ministers and Central Bank Governors Meeting - Malpass, David (World Bank, Washington, DC, 2020)
World Bank Group President David Malpass said that while some countries are recovering, the pandemic is still taking a terrible toll, with poverty levels rising sharply. He highlighted on the health emergency response programs in one hundred twelve countries using a fast-track mechanism that is now able to access a further window of twelve billion in funding for vaccine purchases and delivery. He also mentioned that the World Bank is already at work in cooperation with WHO, UNICEF, the Global Fund and GAVI on rapid vaccine deployment readiness assessments for one hundred countries. He spoke about IFC working in coordination with CEPI to invest a further four billion in manufacturing and distribution of vaccines and products that support vaccination programs. He recognized that fragile conflict and violence (FCV) states are most in need, and World Bank's engagement with them. Under his Presidency, the World Bank Group has invested more in climate finance than at any time in its history. He mentioned that IDA is frontloading its financing to make more resources available for the poorest countries. He highlighted on an important step that the G20 call on DSSI beneficiary countries to commit to disclose all public sector financial commitments. The Development Committee that asked the Bank and the IMF to propose more actions to address the unsustainable debt burdens of low- and middle-income countries. He concluded that the fuller transparency is the only way to balance the interests of the people with the interests of those signing the debt and investment contracts.